(untitled) ([Germany], 2019)
A quick introduction to central tools and techniques. The different chapters each correspond to a 1 to 2 hours course with increasing level of expertise, from beginner to expert.
Keywords: Python (Computer program language),Python (Ngôn ngữ lập trình máy tính)